Local Innovations Using Traditional Vegetables to Improve Soil Quality - World Bank (World Bank, Washington, DC, 2012)
Prior to the 1970s, parish farmers predominantly produced traditional vegetable crops for home consumption. At that time local farmers did not produce exotic vegetables, such as cabbages, carrots, lettuce, etc. which were produced on plantations and mainly consumed by the European and Asian populations, or exported. The vegetables that the rural African population produced for consumption as local foodstuff were considered traditional vegetables.